Pemodelan Pertumbuhan Ekonomi Menggunakan Bayesian Spatial Durbin Model - Soraya, Siti; Setiawan, Setiawan; Rahayu, Santi Puteri (Teknomatika, 2017)
Economic growth was a measure of economic development in a region. High economic growth was the key to the welfare of society. Indicators of economic growth was GDP. High GDP indicates that the economic growth of the region was being well. One of the areas in Indonesia where coined the GDP was quite good and at the same time become the third largest contributor was the province of East Java. In this research, modeling of GDP by using Bayesian approach Spatial Durbin Model (SDM). The data was used the GDP of each regencycity in East Java as the response variable and the factors that give impact the amount of labor, capital value and the magnitude of the electrification ratio as a predictor variable. The results showed that there was a spatial dependencies and spatial heterogeneity in GDP for the districtcity in East Java province. From the analysis carried out showed that  was positive and not significant at the 10 level. Results of the estimation parameters was known that the amount of labor, capital  value  and  the  amount  of  labor  which  is  weighted  variables  that significantly influence the model. Thus, the GDP of a region in East Java was influenced by the amount of labor, capital value and the amount of labor that GDP weighted and other neighboring regions.  KeywordsBayesian, Heteroskedastisitas, GDP, Spatial Durbin Model (SDM)